Biosynthesis of the Polycyclic System in the Antifungal HSAF and Analogues from Lysobacter enzymogenes. (25th April 2018) - Li, Yaoyao; Wang, Haoxin; Liu, Yan; Jiao, Yujie; Li, Shanren; Shen, Yuemao; Du, Liangcheng
Abstract: The biocontrol agent Lysobacter enzymogenes produces polycyclic tetramate macrolactams (PoTeMs), including the antifungal HSAF. To elucidate the biosynthesis of the cyclic systems, we identified eleven HSAF precursors/analogues with zero, one, two, or three rings through heterologous expression of the HSAF gene cluster. A series of combinatorial gene expression and deletion experiments showed that OX3 is the "gatekeeper" responsible for the formation of the first 5‐membered ring from lysobacterene A, OX1 and OX2 are responsible for formation of the second ring but with different selectivity, and OX4 is responsible for formation of the 6‐membered ring. In vitro experiments showed that OX4 is an NADPH‐dependent enzyme that catalyzes the reductive cyclization of 3‐dehydroxy alteramide C to form 3‐dehydroxy HSAF. Thus, the multiplicity of OX genes is the basis for the structural diversity of the HSAF family, which is the only characterized PoTeM cluster that involves four redox enzymes in the formation of the cyclic system. Abstract : Vier Gene ( OX1–OX4 ), die für NADPH‐abhängige Redoxenzyme kodieren, diktieren die strukturelle Diversität der antifungalen HSAF‐Familie von polycyclischen Tetramat‐Makrolactamen aus dem Gram‐negativen Bakterium Lysobacter enzymogenes, einem wirksamen Biokontrollagens und proliferativen Produzenten bioaktiver Naturstoffe.